Assessment of the Implementation of Physics Curriculum in Public Secondary Schools in Calabar Metropolis, Cross River State, Nigeria - Ayeshung Imoniri; Offiong Efanga (Teacher Education and Curriculum Studies, 2026)
This study examined the curriculum implementation gap in the teaching of Physics in public secondary schools in Calabar Metropolis, Cross River State, Nigeria, and investigated the influence of teacher-related factors on curriculum implementation. The study was guided by two hypotheses. A descriptive survey research design was adopted, and a census of 55 Physics teachers from 26 public secondary schools was used. Data were collected using a 30-item structured curriculum implementation checklist. The checklist adopted a four-point Likert scale of Strongly Agree, Agree, Disagree and Strongly Disagree. The instrument was validated by specialists in science education and curriculum study. The internal consistency of the instrument was assessed using Cronbach Alpha reliability which produced a reliability coefficient of 0.72. Multiple linear regression analysis was employed to test the hypotheses at a 0.05 level of significance. Findings revealed significant curriculum implementation gap in Physics teaching. Result also revealed that teacher-related factors significantly influenced physics curriculum implementation in physics teaching. The study concluded that Physics curriculum implementation is significantly constrained by both curriculum implementation gaps and teacher-related factors. It was recommended that sustained professional development, improved laboratory facilities, and enhanced curriculum orientation programs be implemented to strengthen effective curriculum delivery in public secondary schools in Calabar Metropolis.